2004
DOI: 10.1007/s00213-004-1824-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrinological and neuropsychological correlates of dopaminergic function in nicotine dependence

Abstract: Smoking is significantly associated with a reduced sensitivity of central DA D2 receptors. This alteration of dopaminergic sensitivity is stable even after 12 h of abstinence from nicotine. Therefore, the hypothesis that the motivational impairment during withdrawal from nicotine is associated with an altered sensitivity of central DA D2 receptors cannot be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
2
10
0
1
Order By: Relevance
“…Recently, Colilla et al (2005) found overtransmission of the Met allele in female exsmokers suggesting that the Met allele is correlated with successful quitting whereas in our results the Met allele is associated with ND. Our results are in line with findings from both animal and human studies which show that reward processes are mediated by dopaminergic pathways from the ventral tegmental area to nucleus accumbens and frontal cortex (Kalivas, 1993), and that nicotine stimulates the release of dopamine from neurons (Corrigall et al, 1992;Nisell et al, 1994;Pontieri et al, 1996;Balfour et al, 2000;Smolka et al, 2004). Therefore, individuals with low-activity COMT haplotypes may experience a longer-lasting and more effective dopamine release in the brain, thereby increasing the magnitude and/or duration of reward derived from smoking and the risk of becoming nicotine dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Colilla et al (2005) found overtransmission of the Met allele in female exsmokers suggesting that the Met allele is correlated with successful quitting whereas in our results the Met allele is associated with ND. Our results are in line with findings from both animal and human studies which show that reward processes are mediated by dopaminergic pathways from the ventral tegmental area to nucleus accumbens and frontal cortex (Kalivas, 1993), and that nicotine stimulates the release of dopamine from neurons (Corrigall et al, 1992;Nisell et al, 1994;Pontieri et al, 1996;Balfour et al, 2000;Smolka et al, 2004). Therefore, individuals with low-activity COMT haplotypes may experience a longer-lasting and more effective dopamine release in the brain, thereby increasing the magnitude and/or duration of reward derived from smoking and the risk of becoming nicotine dependent.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, smoking withdrawal seems to be associated with a hypo-dopaminergic state in humans (Smolka et al, 2004) and animals (Fung et al, 1996;Epping-Jordan et al, 1998), which could lead to abnormal neural activity in areas implicated in cue-reactivity, in particular the DLPFC, ACC, and striatum.…”
Section: Introductionmentioning
confidence: 99%
“…Acute nicotine produces both rewarding and aversive stimulus properties (Laviolette and van der Kooy, 2004;Sellings et al, 2008;Wilkinson and Bevins, 2008). Dopaminergic signaling is involved in acute nicotine aversion (Laviolette and van der Kooy, 2003;Tan et al, 2009) and chronic nicotine motivation (Bruijnzeel and Markou, 2005;Kenny and Markou, 2001;Laviolette et al, 2008;Smolka et al, 2004); however, little is known regarding the role of dopaminergic signaling in the opponent motivational processes of acute and chronic nicotine.…”
Section: Introductionmentioning
confidence: 99%